Development of a Science Literacy Instrument with a Tourism Context in Sumenep Regency in Environmental Education Lectures: Pengembangan Instrumen Literasi Sains Berkonteks Wisata Kabupaten Sumenep pada Perkuliahan Pendidikan Lingkungan Hidup - Yamin, Yamin; Nur Qomaria; Try Hartiningsih; Sardi, Pramudista; Muhamad Asyroful Ibad (SEJ (Science Education Journal), 2024)
This research aims to produce a product in the form of a scientific literacy instrument in the local tourism context of Sumenep Regency during Environmental Education (PLH) lectures. This research uses research and development methods (Research & Development) using the ADDIE model which includes analysis, design, development, implementation, evaluation. The instrument used in this research was a test. The aspect measured is scientific literacy ability. The results of the question validation obtained an accumulated score with a percentage of 79.47 in the category "very valid." The results of attitude validation obtained an accumulation with a percentage of 61.60 in the "valid" category. The results of the one to one trial obtained a score of 63 in the "Good" category. And the results of the small group trial obtained a score of 67 in the "Good" category. Based on these results, it can be concluded that the scientific literacy instrument in the tourism context of Sumenep district is suitable for use as a tool for evaluating scientific literacy skills in Environmental Education lectures. Low scientific literacy skills are a problem that must be addressed immediately for the advancement of superior and quality human resources. One of the causes of low scientific literacy is the lack of developed scientific literacy instruments. It is hoped that the development of a scientific literacy instrument in the tourism context of Sumenep district will be able to become a tool for measuring students' scientific literacy abilities on a regular basis.